Policy coalitions in food systems transformation - Swinnen, Johan; Resnick, Danielle (International Food Policy Research Institute, 2023)
Coalitions—or a set of individuals and groups with shared policy preferences—lie at the heart of political economy.¹ They are also often considered central to policy change. For instance, in 1999, the president of the World Bank argued that many of the world’s most intractable development issues could only be tackled by marshaling “coalitions for change” (Wolfensohn 1999). The implied positive potential of coalitions was reiterated during the 2021 UN Food Systems Summit, where coalitions were seen as a fundamental tool for addressing the multi-sectoral and multi-scalar nature of food systems transformation. In fact, more than two dozen coalitions were formed to address various elements of the food system, from halting deforestation to improving data to enhancing wages for food system workers.